Analisis Perilaku SKPD dan DPRD dalam Proses Penyusunan Penganggaran dengan Fenomenologi - Lalu Takdir Jumaidi (Jurnal Riset Akuntansi, 2019)
The purpose of this research is to understanding the behavior of SKPD (executive) and DPRD(legislative) members on arranging Mataram public sector budged. This research is use Discriptive cualitatif and reaserch approach is The phenomenology. Paradigm method of this research is interpretive. Based on the phenomenology analysis the writer found 3 basic underlying behaviours which are false participation, low social awareness, and budgeting not pro poor. Participation behavior, low social awareness and budgeting not pro poor, the result are opposite of local sensible value. This executive and legislative behavior arrange the unfair budget can be happened because accumulation of false participation, low social awareness, huge power to control the budgeting without being offset by the balance of the division of authority to the community to be able to guard the nets tight budget processes. This condition can be proved with budget product that shows not pro poor.